Metformin - Mihaela Pantea Stoian, Anca; Rizzo, Manfredi (IntechOpen, 2020)
The book "Metformin" aims to bring to light new concepts and trends related to the many metformin therapeutic features. After a history of over 60 years, with moments of decline and spectacular returns, metformin can now be regarded as a universal panacea, the valences of its therapeutics being increasingly appreciated, both in the background treatment of diabetes and pre-diabetes, but also in reproductive pathology, cancer, cardiovascular disease, and antiageing. In this respect, the mechanisms of action and the pharmacodynamics of metformin seem to be incompletely known, a number of current studies have revealed new action valences.